(untitled) (Global Conference on Medical and Health Sciences, 2026)
Breast cancer is a multifactorial disease influenced by both environmental and genetic determinants. Among hereditary factors, mutations in the BRCA1 and BRCA2 genes represent the most significant genetic predisposition associated with increased lifetime risk of breast and ovarian cancers. Women carrying pathogenic BRCA mutations face a substantially higher probability of developing early-onset and biologically aggressive breast cancer compared to the general population. Therefore, early identification of high-risk individuals through genetic screening has become a critical component of modern oncology. Genetic screening and BRCA testing enable risk stratification, personalized surveillance strategies, and implementation of preventive interventions, including intensified imaging follow-up, chemoprevention, and prophylactic surgery. Advances in molecular diagnostics, including next-generation sequencing, have improved accessibility and accuracy of mutation detection. Early identification of mutation carriers not only benefits individual patients but also allows cascade testing among family members, contributing to broader preventive impact. In transitional healthcare systems, however, the integration of genetic screening into routine clinical practice remains limited due to restricted access to molecular testing, high costs, and insufficient awareness among both healthcare providers and the population. Expanding genetic counseling services and incorporating risk-based screening protocols may significantly improve early detection rates and reduce mortality among genetically predisposed women. This article analyzes the clinical significance of BRCA mutations, evaluates the role of genetic screening in early risk identification, and discusses practical considerations for implementing genetic testing programs within emerging healthcare environments.